Download presentation
Presentation is loading. Please wait.
1
CHAPTER 4 The Laplace Transform
2
Contents 4.1 Definition of the Laplace Transform
4.2 The Inverse Transform and Transforms of Derivatives 4.3 Translation Theorems 4.4 Additional Operational Properties 4.5 The Dirac Delta Function
3
4.1 Definition of Laplace Transform
Basic Definition If f(t) is defined for t 0, then the improper integral (1) If f(t) is defined for t 0, then (2) is said to be the Laplace Transform of f. DEFINITION 4.1 Laplace Transform
4
Example 1 Evaluate L{1} Solution: Here we keep that the bounds of integral are 0 and in mind. From the definition , s> Since e-st 0 as t , for s > 0.
5
Example 2 Evaluate L{t} Solution , s>0
6
Example 3 Evaluate L{e-3t} Solution
7
Example 4 Evaluate L{sin 2t} Solution
8
Example 4 (2) Laplace transform of sin 2t ↓
9
L.T. is Linear We can easily verify that (3)
10
(a) (b) (c) (d) (e) (f) (g) Transform of Some Basic Functions
THEOREM 4.1 Transform of Some Basic Functions
11
A function f(t) is said to be of exponential order,
DEFINITION 4.2 A function f(t) is said to be of exponential order, if there exists constants c>0, M > 0, and T > 0, such That |f(t)| Mect for all t > T. See Fig 4.2, 4.3. Exponential Order
12
Fig 4.2
13
Examples See Fig 4.3
14
Fig 4.4 A function such as is not of exponential order, see Fig 4.4
15
If f(t) is piecewise continuous on [0, ) and of
THEOREM 4.2 If f(t) is piecewise continuous on [0, ) and of exponential order, then L{f(t)} exists for s > c. Sufficient Conditions for Existence
16
Fig 4.1
17
Example 5 Find L{f(t)} for Solution
18
4.2 If F(s)=L(f(t)), then f(t) is the inverse Laplace transform of F(s) and f(t)=L(F(s))
THEOREM 4.3 (a) (b) (c) (d) (e) (f) (g) Some Inverse Transform
19
Example 1 Find the inverse transform of (a) (b) Solution (a) (b)
20
L -1 is also linear We can easily verify that (1)
21
Example 2 Find Solution (2)
22
Example 3: Partial Fraction
Find Solution Using partial fractions Then (3) If we set s = 1, 2, −4, then
23
Example 3 (2) (4) Thus (5)
24
Uniqueness of L -1 Suppose that the functions f(t) and g(t) satisfy the hypotheses of Theorem 4.2, so that their Laplace transform F(s) and G(s) both exist. If F(s)=G(s) for all s>c (for some c), then f(t)=g(t) whenever on [0, + ) both f and g are continuous.
25
Transform of Derivatives
(7) (8)
26
If are continuous on [0, ) and are of
THEOREM 4.4 If are continuous on [0, ) and are of Exponential order and if f(n)(t) is piecewise-continuous On [0, ), then where Transform of a Derivative
27
Solving Linear ODEs Then (9) (10)
28
We have (11) where
30
Example 4: Solving IVP Solve Solution (12) (13)
31
Example 4 (2) We can find A = 8, B = −2, C = 6 Thus
32
Example 5 Solve Solution (14) Thus
33
4.3 Translation Theorems If f is piecewise continuous on [0, ) and of
exponential order, then lims L{f} = 0. Behavior of F(s) as s → Proof
34
F(s) by s-a If L{f} = F(s) and a is any real number, then
THEOREM 4.6 If L{f} = F(s) and a is any real number, then L{eatf(t)} = F(s – a), See Fig 4.10. Translation on the s-axis Proof L{eatf(t)} = e-steatf(t)dt = e-(s-a)tf(t)dt = F(s – a): replacing all s in F(s) by s-a
35
Fig 4.10
36
Example 1 Find the L.T. of (a) (b) Solution (a) (b)
37
Inverse Form of Theorem 4.6
(1) where
38
Parttial Fraction To perform the inverse transform of R(s)=P(s)/Q(s):
Rule 1: Linear Factor Partial Fractions Rule 2: Quadratic Factor Partial Fractions
39
Example 2 Find the inverse L.T. of (a) (b)
Solution (a) we have A = 2, B = (2)
40
Example 2 (2) And (3) From (3), we have (4)
41
Example 2 (3) (b) (5) (6) (7)
42
Example 3 Solve Solution
43
Example 3 (2) (8)
44
Example 4 Solve Solution
45
Example 4 (2)
46
The Unit Step Function U(t – a) defined for is Unit Step Function
DEFINITION 4.3 The Unit Step Function U(t – a) defined for is Unit Step Function See Fig 4.11.
47
Fig 4.11
48
Fig Fig 4.13 Fig 4.12 shows the graph of (2t – 3)U(t – 1). Considering Fig 4.13, it is the same as f(t) = 2 – 3U(t – 2) + U(t – 3),
49
Also a function of the type. (9) is the same as
Also a function of the type (9) is the same as (10) Similarly, a function of the type (11) can be written as (12)
50
Example 5 Express in terms of U(t). See Fig 4.14.
Solution From (9) and (10), with a = 5, g(t) = 20t, h(t) = 0 f(t) = 20t – 20tU(t – 5)
51
Fig 4.14
52
Consider the function (13) See Fig 4.15.
53
Fig 4.15
54
If F(s) = L{f}, and a > 0, then L{f(t – a)U(t – a)} = e-asF(s)
THEOREM 4.7 If F(s) = L{f}, and a > 0, then L{f(t – a)U(t – a)} = e-asF(s) Second Translation Theorem Proof
55
Let v = t – a, dv = dt, then If f(t) = 1, then f(t – a) = 1, F(s) = 1/s, (14) eg: The L.T. of Fig 4.13 is
56
Inverse Form of Theorem 4.7
(15)
57
Example 6 Find the inverse L.T. of (a) (b) Solution (a) then (b) then
58
Alternative Form of Theorem 4.7
Since , then The above can be solved. However, we try another approach. Let u = t – a, That is, (16)
59
Example 7 Find Solution With g(t) = cos t, a = , then g(t + ) = cos(t + )= −cos t By (16),
60
Example 8 Solve Solution We find f(t) = 3 cos t U(t −), then (17)
61
Example 8 (2) It follows from (15) with a = , then Thus (18) See Fig 4.16
62
Fig 4.16
63
4.4 Additional Operational Properties
Multiplying a Function by tn that is, Similarly,
64
If F(s) = L{f(t)} and n = 1, 2, 3, …, then
THEOREM 4.8 If F(s) = L{f(t)} and n = 1, 2, 3, …, then Derivatives of Transform
65
Example 1 Find L{t sin kt}
Solution With f(t) = sin kt, F(s) = k/(s2 + k2), then
66
Different approaches Theorem 4.6: Theorem 4.8:
67
Example 2 Solve Solution or From example 1, Thus
68
Convolution A special product of f * g is defined by and is called the convolution of f and g. Note: f * g = g * f
69
IF f(t) and g(t) are piecewise continuous on [0, ) and
THEOREM 4.9 IF f(t) and g(t) are piecewise continuous on [0, ) and of exponential order, then Convolution Theorem Proof
70
Holding fixed, let t = + , dt = d The integrating area is the shaded region in Fig Changing the order of integration:
71
Fig 4.32
72
Example 3 Find Solution Original statement = L{et * sin t}
73
Inverse Transform of Theorem 4.9
L-1{F(s)G(s)} = f * g (4) Look at the table in Appendix III, (5)
74
Example 4 Find Solution Let then
75
Example 4 (2) Now recall that sin A sin B = (1/2) [cos (A – B) – cos (A+B)] If we set A = k, B = k(t − ), then
76
Transform of an Integral
When g(t) = 1, G(s) = 1/s, then
77
Examples:
78
Periodic Function f(t + T) = f(t): periodic with period T
If f(t) is a periodic function with period T, then THEOREM 4.10 Transform of a Periodic Function
79
Proof Use change of variable
80
Example 7 Find the L. T. of the function in Fig 4.35.
Solution We find T = 2 and From Theorem 4.10,
81
Fig 4.35
82
Example 8 The DE (13) Find i(t) where i(0) = 0, E(t) is as shown in Fig 4.35. Solution or (14) Because and
83
Assuming R=1ohm, L=1 henry
Then i(t) is described as follows and see Fig 4.36: (15)
84
Fig 4.36
85
4.5 The Dirac Delta Function
Unit Impulse See Fig 4.43(a). Its function is defined by (1) where a > 0, t0 > 0. For a small value of a, a(t – t0) is a constant function of large magnitude. The behavior of a(t – t0) as a 0, is called unit impulse, since it has the property See Fig 4.43(b).
86
Fig 4.43
87
The Dirac Delta Function
This function is defined by (t – t0) = lima0 a(t – t0) (2) The two important properties: (1) (2) , x > t0
88
Proof The Laplace Transform is
THEOREM 4.11 For t0 > 0, Transform of the Dirac Delta Function Proof The Laplace Transform is
89
When a 0, (4) is 0/0. Use the L’Hopital’s rule, then (4) becomes 1 as a 0. Thus , Now when t0 = 0, we have
90
Example 1 Solve subject to (a) y(0) = 1, y’(0) = 0 (b) y(0) = 0, y’(0) = 0 Solution (a) s2Y – s + Y = 4e-2s Thus y(t) = cos t + 4 sin(t – 2)U(t – 2) Since sin(t – 2) = sin t, then (5) See Fig 4.44.
91
Fig 4.44
92
Example 1 (2) (b) Thus y(t) = 4 sin(t – 2)U(t – 2) and (6)
93
Fig 4.45
Similar presentations
© 2024 SlidePlayer.com. Inc.
All rights reserved.